(3JfXje GdefGaSIs - (3MSjf(B, (3GdeGMjs ((3GdbGgQI(B:s (3OGQ GdfgVI(B,s, 2003)
(3aj gPG GdcJGH JMOjO GdShb GdJfGaSjI , GdShb GdfhYjI , GdShb GdLZQGajI GdbhGYO VHW GdShb GdJfGaSjI , GdGJaGbGJ Ch GdeeGQSGJ GdVGQI HbhGYO JMOjO GdGSYGQ ,dGJaGbGJ Ch GdeeGQSGJ GdVGQI HbhGYO GdOMhd Ch GdHbGA aj GdShb GdJfGaSjI , GdGJaGbGJ Ch GdeeGQSGJ GdVGQI , GdGJaGbGJ Ch GdeeGQSGJ GdUGQIs
(3HjHdjhZQGajG (B: (3U(B. 82s
Keywords: (3GdCShGbs; (3GdefGaSIs